EFEKTIVITAS PENGAWASAN KEPABEANAN IMPOR TERKAIT DENGAN KEBIJAKAN ASEAN-CHINA FREE TRADE AREA DI KANTOR PELAYANAN UTAMA BEA DAN CUKAI TIPE A TANJUNG PRIOK - Ahmad Djunaidi; Aji Prasetyo; Reza Kurnia Putra (Jurnal Pajak Vokasi (JUPASI), 2019)
The ACFTA policy, which makes it easier for users of imported goods from China, has caused some cases of importers violating the ACFTA policy provisions by smuggling illegal goods from China. This study aims to determine the effectiveness of import kepabenan supervision related to the policy of ACFTA in Main Service Office of Customs and Excise Type A Tanjung Priok related to the number of smuggled goods and illegal goods entering Indonesia utilizing ACFTA policy, inhibiting factors and driving factors what are simultaneously interconnected with the level of effectiveness of import customs supervision related to ACFTA policy. The research approach used is descriptive qualitative. From the research result, it is known that import supervisory supervision related to ACFTA policy in Main Service Office of Customs and Excise Type A Type A Tanjung Priok is still not effective, with inhibiting factor that is inadequate infrastructure and human resources which is not proportional to work volume so that supervision becomes less intensive, namely automatic tracking system and Product Intelligence Result Memorandum in conducting supervision and import standards that have been set by Customs.